THE EFFECT OF DISCOVERY LEARNING ON READING COMPREHENSION IN DESCRIPTIVE TEXT OF THE FIRST YEAR STUDENTS OF SMAN 1 PANGKALAN KERINCI - Reka Nofianti; Eliwarti Eliwarti; Erni Erni (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : This study aims to find out the effect of discovery learning on reading comprehension of the first year students of SMAN 1 Pangkalan Kerinci in descriptive text.The data were collected in July to August. The population of this research is the first year students of SMAN 1 Pangkalan Kerinci. The number of sample is 35 students who are chosen by using cluster random sampling technique. This research is a pre experimental research with one group pre-test post-test design. The instrument to collect the data was multiple choice tests with 25 questions. The result of the data analysis showed that the mean score of pre-test is 64,8 while in post-test is 73. 05. It showed that the mean score of post-test was higher than pre-test. Hence, there is a significant effect effect of discovery learning on reading comprehension of the first year students of SMAN 1 Pangkalan Kerinci in descriptive text.Keywords: Pre Experimental, Discovery Laerning, Reading Comprehension, Senior High School, First Year Students.